Systematic Review Of Spiritual Impact Of Recovery Stroke Outcome - Dwi Mulianda; Margiyati Margiyati; Chandra Bagus Ropyanto (Pusat Riset dan Inovasi Nasional, 2023)
Numerous functional impairments that stroke patients face lead to a decreased quality of life, powerlessness, and suicidal thoughts. Spirituality-based stroke recovery interventions may have mechanisms that aid in the healing process and can help create more thorough and efficient stroke rehabilitation programs. Methodology This study is a review that is systematic. The researchers used Google Scholar databases to look for data sources. The terms